Ligating the varicose vein trunk for bleeding stomal varices in portal hypertension: a case report - Sun, Jialiang; Tan, Zhanhai; Zhang, Jifa (Frontiers in Medicine, 2025)
IntroductionIn colostomy-related complications, variceal hemorrhage particularly induced by cirrhosis and portal hypertension is seldom encountered. The onset of peristome variceal hemorrhage necessitates swift and effective intervention to prevent potentially life-threatening outcomes such as hemorrhagic shock and recurrent stoma bleeding.Case presentationThis report details a case of repeated varicose vein hemorrhage around the stoma in a patient with liver cirrhosis. Abdominal enhanced CT images revealed that the stomal varices originated from a branch of the inferior mesenteric vein, with vein balls encompassing the stoma. The patient was acquired with successful hemostasis through high ligation of the various vein primary trunk, and stripping of the vein balls around stoma, along with intracutaneously suturing of the sub-abdominal wall varicose veins. When the stoma bag was changed it was observed that the skin surrounding the stoma was flat, the mucosa was red, and the varicose venous mass had vanished. After 2 months of follow-up, the stomal function was doing well without any rebleeding episodes.ConclusionIn this instance, decompensated cirrhosis led to stomal varices and recurrent bleeding, which was initially managed with local compression and suture therapy but resulted in rebleeding. Our team’s approach through blocking the primary trunk of variceal vein via a minimal incision under local anesthesia may offer a new treatment strategy for patients with poor liver function who cannot withstand the trauma associated with general anesthesia and major surgery.